1999
DOI: 10.1590/s0104-14281999000400025
|View full text |Cite
|
Sign up to set email alerts
|

Filmes ópticos poliméricos fluorados com índice de refração gradual

Abstract: Filmes finos de PMMA foram preparados a partir de solução e expostos ao plasma de CF4+H2, visando mudar o Índice de Refração (I.R.) da superficie do PMMA através da fluoração. Os filmes de PMMA expostos ao plasma, denominados de filmes ópticos, foram caracterizados usando as técnicas: ESCA, RBS, FTIR, gravimetria, ângulo de contato, refratometria e elipsometria. Os resultados revelaram que as superfícies de PMMA foram revestidas com uma fina camada de hidrofluorcarbono polimérico, com espessuras variando entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 3 publications
0
6
0
6
Order By: Relevance
“…However, after of the plasma treatment the refractive index of 1.41 was attained. In similar cases, when plasma of CF 4 + H 2 was deposited on PMMA, the refractive index was 1.43 [26] . Thus, plasma treatment used in this study to produce polymeric optical films allows polymer waveguides to be manufactured, with a numerical aperture (NA) near 0.5.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, after of the plasma treatment the refractive index of 1.41 was attained. In similar cases, when plasma of CF 4 + H 2 was deposited on PMMA, the refractive index was 1.43 [26] . Thus, plasma treatment used in this study to produce polymeric optical films allows polymer waveguides to be manufactured, with a numerical aperture (NA) near 0.5.…”
Section: Resultsmentioning
confidence: 91%
“…Usually, the cladding has slightly smaller refractive index than pure PMMA. Bartoli et al [26] observed greater speed and higher quality of transmission in polymeric optical fibers. PMMA was coated with hydrofluorocarbon (HFC) plasma.…”
Section: Resultsmentioning
confidence: 98%
“…Em estudo conduzido por Bartoli et al [21] são analisados potenciais ganhos de velocidade e reduções nas perdas de qualidade de transmissão em fibras ópticas poliméricas. Para tanto, foi realizado o revestimento (P 4 ) do poli metacrilato de metila do núcleo da fibra com hidrofluorcarbono (HFC) por meio de polimerização por plasma de CF 4 associado a hidrogênio.…”
Section: Etapa De Revestimentounclassified
“…Como se pôde perceber nas pesquisas de Noda e Koike [17] , Koike e Asai [20] e Bartoli et al [21] , há acréscimo nos custos de produção em função dos materiais ou Quadro 1. Relação entre comprimento de onda e coeficiente de atenuação em fibras vítreas e poliméricas.…”
Section: Etapa De Revestimentounclassified
See 1 more Smart Citation